Digital competencies for municipalities – Findings from Switzerland as a role model for smart regions within the European Union member states - Christian SCHACHTNER; Nadine BAUMANN (Smart Cities and Regional Development Journal)
The study shows that e-government services, cybersecurity and digital document management have been identified as key priorities for digitization in Swiss municipalities, which is crucial for the development of smart regions. This study aimed to assess the needs for certified digital competencies among decision-makers in small Swiss municipalities and cities. It sought to identify relevant digital transformation topics, required competencies, recruitment practices, training needs, and collaborations. While smart city initiatives have gained traction in larger urban areas, less attention has been paid to digitalization efforts in smaller municipalities. This study helps to fill that gap examining the specific needs and challenges of smaller Swiss communities. An online survey was conducted among 1,221 German-speaking Swiss municipalities in February 2024, with 215 responses (17.6% response rate). The survey covered topics such as digital transformation priorities, competencies, recruitment, training needs, and partnerships. Key findings include: E-government services, cybersecurity, and digital document management were top digitalization priorities; 61% of municipalities have a person responsible for digitalization efforts; Personal competencies like curiosity and willingness to learn were highly valued; Only 32% use competency-based job profiles in recruitment; There is significant interest in further training on digital transformation topics. The results highlight the need for targeted training and competency development for digitalization leaders in smaller municipalities. They also reveal opportunities to improve recruitment practices and leverage partnerships. This study provides valuable insights to inform the development of tailored training programs and competency frameworks for digital transformation in small Swiss municipalities. It contributes to the broader smart cities literature by examining the unique needs of smaller communities often overlooked in urban-centric research.